The Role of Sport in City Branding: A Case Study of Ottawa - Pan, Hao (Université d'Ottawa / University of Ottawa, 2019)
In the first decades of the twenty-first century, cities around the globe are increasingly seeking to use various branding techniques to uniquely position themselves on the world stage. They do this via points of difference they hope corporations, institutions, and individuals recognize as having value; the intention being a variety of investments in those cities, primarily economic, but, often, via the ingress of human talent. That high-performance and mega sport events (e.g., IOC Olympic Games, FIFA World Cup, and F1 Grands Prix) have often been used to provide such points of difference is very well documented. However, the use of other, less high profile, forms of community-based recreational sport and physical activity in city branding activity has not received much attention. This thesis aims to begin to redress that imbalance. Initially, the thesis describes sporting activities as taking place on a continuum, and proposes a conceptual model to illustrate the notion: the continuum’s end points are labelled ‘upper-case’ for high-performance sport, and ‘lower-case’ for more community-based activities. Subsequently, and using a sample of senior leaders involved in the management of the municipal branding of Canada’s national capital, and various other engaged individuals, the thesis examines perceptions of various modes of sporting activity in the city branding process. Results indicate lower-case community-based recreational sport and physical activity experienced in the city can serve a variety of purposes. Firstly, it can encourage citizen engagement in the city, which could further stimulate ongoing branding activity on behalf of the city via resident’s word-of mouth conversations. Such activity would necessarily reflect individual’s lived experience of the city. Secondly, the notion of quality of life amongst residents emerged from the data. This would appear to be a positive aspect of city living that could be used to actively promote the city to a wide range of corporate and individual audiences seeking to optimise their investment – be it financial or personal.
Keywords: city branding; sport management; marketing; branding